The role of the aortic area in type A aortic dissection. (July 2021) - Wang, Ziyan; Tian, Shengwei; Yu, Long; Ma, Xiang; Xing, Yan; Ma, Xiaoli
Graphical abstract: Highlights: We suggest that the true lumen area and the ratio of true lumen area to the aortic area may be a potential cause of the aortic rupture. The intensity of swirl was used as an index of blood flow disorder. Two cases of type A dissection before and after operation were used as experimental verification. Abstract: Aortic dissection (AD) is a cardiovascular disease with a high mortality rate. At present, there is no practical guidance for predicting and preventing aortic dissection, which is usually guided by clinicians' experience. The purpose of this study was to analyze the correlation between the maximum true lumen area of ascending aorta and the severity of type A aortic dissection in Stanford type A dissection. Fifteen patients were divided into the aortic rupture group, aortic dissection group, and healthy control group. The hemodynamic analysis of CTA data of two cases before and after the operation was used for experimental verification. The results showed that the maximum true lumen area of ascending aorta was negatively correlated with the risk degree. We suggest that the maximum true lumen area of the ascending aorta should be considered a predictor of rupture risk in Stanford A aortic dissection.